Performance characteristics of viscoseals in laminar and turbulent flow regimes. (October 2017) - Souchet, Dominique; Jarray, Mohamed; Fatu, Aurelian
Abstract: In this paper, a numerical study of a viscoseal operating behavior, under laminar and turbulent regime, is presented. The finite element method is used under different hydrodynamic regimes associated to lubrication assumptions. The theoretical model, based on the classical Reynolds equation uses the approach of average value of turbulent coefficient. In order to include the film rupture and reformation, the Reynolds equation is modified using a mass conservative algorithm. A transition zone between laminar and turbulent flow is modelled. A comparison is done between numerical and experimental results on different seals geometries and the overall comparisons are good. Next, the proposed model is used to predict viscoseal behaviors in terms of friction and seal capability for different operating conditions. Highlights: A finite element model is developed to predict visoseal performance under laminar and turbulent regime. The results obtained numerically are close to the experimental values. The influence of the seal geometry and operating conditions on the sealing length and friction torque is investigated.